Construction and function of a highly efficient supramolecular luminescent system. (6th December 2016) - Liu, Yingjie; Ma, Suqian; Xu, Bin; Tian, Wenjing
Abstract : Aggregation-induced emission (AIE) provides a new way of achieving highly efficient luminescent materials. In this contribution, the self-assembly behavior, molecular stacking structure and photophysical properties of two polymorphs of a supramolecular co-crystal (C1 and C2) are investigated. The block-like crystal C1, packed in segregated stacking with strong π–π interactions between theH andG molecules, shows weak green emission with a low efficiency ( Φ F ) of 2%. In comparison, the needle-like crystal C2, packed in segregated stacking with no obviously strong intermolecular interactions, shows bright yellow emission. More importantly, C1 exhibits mechanochromic behavior.